1990
DOI: 10.1128/mcb.10.12.6512
|View full text |Cite
|
Sign up to set email alerts
|

Expression of chimeric tRNA-driven antisense transcripts renders NIH 3T3 cells highly resistant to Moloney murine leukemia virus replication.

Abstract: NIH 3T3 cells infected with Moloney murine leukemia virus (MoMLV) express high levels of virus-specific RNA. To inhibit replication of the virus, we stably introduced chimeric tRNA genes encoding antisense templates into NIH 3T3 cells via a retroviral vector. Efficient expression of hybrid tRNA-MoMLV antisense transcripts and inhibition of MoMLV replication were dependent on the use of a particular type of retroviral vector, the double-copy vector, in which the chimeric tRNA gene was inserted in the 3' long te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 49 publications
1
40
0
Order By: Relevance
“…The transition of such an intracellular inhibitor to in vivo models requires one of two approaches. Gene therapeutic methods utilizing viral constructs may be used to "express" small, therapeutic RNAs following gene transfer into cells (27). Alternatively, an aptamer may be selected de novo with nuclease-resistant nucleotides and delivered locally or systemically.…”
Section: Intimal Hyperplasiamentioning
confidence: 99%
“…The transition of such an intracellular inhibitor to in vivo models requires one of two approaches. Gene therapeutic methods utilizing viral constructs may be used to "express" small, therapeutic RNAs following gene transfer into cells (27). Alternatively, an aptamer may be selected de novo with nuclease-resistant nucleotides and delivered locally or systemically.…”
Section: Intimal Hyperplasiamentioning
confidence: 99%
“…To express ribozymes, RNA polymerase II (pol II) and III (pol III) promoters have been used. RNA pol III-based expression cassettes, containing the tRNA, U6, and adenoviral VA1 promoters, have been extensively used to express small RNAs such as antisense RNAs (Jennings and Molloy 1987;Sullenger et al 1990a), trans-cleaving ribozymes (Ojwang et al 1992), RNA decoys (Sullenger et al 1990b), and siRNAs (Lee et al 2002;Miyagishi and Taira 2002;Paul et al 2002;Sui et al 2002). RNA pol III transcripts accumulate to high levels in transduced mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…44 In fact, studies conducted in the last years have shown that insertion of independent transcriptional units within the two viral LTRs in several instances results in silencing of ribozyme expression, possibly due to competition between the 5 0 LTR Figure 9 Suppression of B3A2 bcr -abl transcripts in primary CML bone marrow cells. Bone marrow mononuclear cells from three patients with CML with the B3A2 bcr -abl translocation were mock transduced ( mock ) or transduced with the retroviral vector expressing the VA1 -RibB3A2 ribozyme ( VA1 -Rib ), and analyzed for bcr -abl gene expression at 2 and 5 days after transduction.…”
Section: Discussionmentioning
confidence: 99%